Who could have seen this coming? The Kenya red cross society and the drought appeal of 2019. Issue 2 (17th May 2021) - Ngoye, Ben Otieno; Saado, Halima; Gachari, Caroline Wambui
Abstract : Learning outcomes: The case will be useful in helping learners: to appreciate concepts in and develop the necessary understanding to apply relevant theories in crisis communications; to identify communications issues along with the evolution of a crisis; to understand the importance and role of a crisis communications team; and to develop skills in writing a crisis communications plan. Case overview/synopsis: The case is a narration of the experiences of the Kenya Red Cross Society (KRCS) as it launched the Kenya drought appeal in March 2019, and the unexpected media and public backlash that ensued. The background is that of an unusual-yet-previously-predicted dry spell, consequent drought and famine, alleged famine-related deaths, mixed signals from the national and county government and a hitherto well-regarded institution (the KRCS) coming in to launch an appeal aimed at raising funds to help alleviate the effects of the prolonged drought and consequent famine in the northern parts of the country. Unfortunately, a major media and public backlash that was not foreseen by KRCS ensued, and it threatened the reputation and very existence of the organization. Drawing on interviews and secondary material in the public domain, the case focuses on how the KRCS navigates the media and public backlash that ensued following the funding appeal. The case is interesting because of the type of organization involved (a not-for-profit institution set up as auxiliary to the government and of good repute), the nature of the problem (reputational crisis and attendant risk management), the setting (a LMIC in sub-Saharan Africa) and the level of analysis (organizational rather than individual decision-making).[AQ1] Complexity academic level: Masters level – MBA, Executive MBA, Master's in Public Management, Master's in Communication and/or similar courses. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 11: Strategy.